Analisis Kandungan Nutrisi Gracilaria Edule (S.G. Gmelin) P.C. Silva dan Gracilaria Coronopifolia J. Agardh untuk Pengembangan Perekonomian Masyarakat Pesisir - Jibrael Narto Bali Ate; Junet Franzisca da Costa; Theresia Pratiwi Elingsetyo S. (Universitas Muhammadiyah Kalimantan Timur, 2017)
Food is a basic human need. Development of nutritious food can be done by utilizing marine natural resources such as seaweed that utilization is not optimal. This study aims to determine the composition of total nutrients (ash content, water content, carbohydrates, fats and proteins) of red seaweed Gracilaria edule (S.G. Gmelin) P.C. Silva and Gracilaria coronopifolia J. Agardh. Proximate analysis using Apriyantono, et al, modified method. Research shows that Gracilaria edule (S.G. Gmelin) P.C. Silva has higher fat content than Gracilaria coronopifolia J. Agardh which is 18,99%; for carbohydrate levels, Gracilaria coronopifolia J. Agardh has higher carbohydrate content than Gracilaria edule (S.G. Gmelin) P.C. Silva is 1.38%; while for protein content has the same protein content that is 0,01%. Water content in seaweed Gracilaria edule (S.G. Gmelin) P.C. Silva higher water content than Gracilaria coronopifolia J. Agardh that is 72,95%%; For ash content, seaweed Gracilaria coronopifolia J. Agardh has higher ash content than Gracilaria edule (S.G. Gmelin) P.C. Silva and for coarse fiber, seaweed Gracilaria edule (S.G. Gmelin) P.C. Silva is higher that is 7.62%. Seaweed contains many essential nutrients necessary for the human body, such as Protein, Carbohydrates and Rough Fiber. Its low fat content and high coarse fiber make seaweed good for consumption. Thus, Gracilaria edule (S.G. Gmelin) P.C. Silva and Gracilaria coronopifolia J. Agardh can be developed into functional food so as to increase market demand and coastal economy can also increase.